2014
DOI: 10.1080/00223131.2014.921582
|View full text |Cite
|
Sign up to set email alerts
|

Early construction and operation of highly contaminated water treatment system in Fukushima Daiichi Nuclear Power Station (I) – Ion exchange properties of KURION herschelite in simulating contaminated water

Abstract: To support the design and operation of the decontamination system using KURION media for the treatment of highly contaminated water accumulated in Fukushima Daiichi Nuclear Power Station, Central Research Institute of Electric Power Industry has urgently carried out many kinds of research and development programs to support the operation of the decontamination system using columns filled with three kinds of KURION media (H, AGH and SMZ). Since the contaminated water at Fukushima Daiichi Nuclear Power Station c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 5 publications
(5 reference statements)
3
14
0
Order By: Relevance
“…Also, the adsorbed amount of Cs in the herschelite column decreased from 1.4 × 10 −2 to 4.2 × 10 −3 mmol/g at approximately 1000 bed volumes with an increase in the sea salt ratio in the feed solution from 1.0 wt% (A-2) to 3.4 wt% (A-5). These results suggest that the adsorption of Cs is hampered by the sea salt ratio, as expected from the equilibrium ion-exchange isotherms obtained for KURION-herschelite in sea salt of different concentrations [17].…”
Section: Effect Of Sea Salt Ratiosupporting
confidence: 70%
See 3 more Smart Citations
“…Also, the adsorbed amount of Cs in the herschelite column decreased from 1.4 × 10 −2 to 4.2 × 10 −3 mmol/g at approximately 1000 bed volumes with an increase in the sea salt ratio in the feed solution from 1.0 wt% (A-2) to 3.4 wt% (A-5). These results suggest that the adsorption of Cs is hampered by the sea salt ratio, as expected from the equilibrium ion-exchange isotherms obtained for KURION-herschelite in sea salt of different concentrations [17].…”
Section: Effect Of Sea Salt Ratiosupporting
confidence: 70%
“…It was reported that Kd (distribution coefficients) of Cs was increased with an increase of V/M, when Cs in the solution was adsorbed with the zeolite [18]. When the isothermal of Cs adsorption was similarly measured in the batch equilibrium test of pure water [17], the adsorbed amount of Cs at V/M = 1000 became larger than that at V/M = 100 as shown Figure 5. However, the adsorbed amount of Cs at V/M=1000 was in almost agreement with that at V/M = 100 in 3.4 wt% sea salt ratio, so the effect of Cs adsorption of V/M was smaller than that in pure water.…”
Section: Effect Of Sea Salt Ratiomentioning
confidence: 85%
See 2 more Smart Citations
“…The core of the system is the vessels filled with zeolite media which adsorbs the Cs in the contaminated water. Just after the accident, Central Research Institute of Electric Power Industry has started various technical supports [1][2][3][4] for Tokyo Electric Power Company to establish the system smoothly and to operate the system safely and stably. The study reported in this article, conducted from June to August in 2011, is about an assessment on the behavior of hydrogen in the used zeolite vessels stored in the same site.…”
Section: Introductionmentioning
confidence: 99%